Chinese parental involvement and class-based inequality in education: the role of social networking sites. Issue 4 (2nd October 2019) - Huang, Hua; Lin, Xun
ABSTRACT: Based on an ethnographic study, this article presents the class-based disparities of Chinese parents' usage of WeChat, the dominating social networking mobile application in China, in their educational involvement. We find that middle-class parents are the privileged ones who have exploited the use of WeChat not only as a medium for communication, but more as a mode of influence. Through WeChat, their various forms of capital are channelled to catalyse changes in their children's education. In contrast, working-class parents tend to act as absent participants in using WeChat for their educational involvement. We argue that WeChat has brought forth the consequence of widening the arena for winning or losing at the educational game for parents from different social classes. We call for corrective policies and guidelines on the usage of WeChat and other SNSs technologies in home–school dynamics.